Applying the Theory of Planned Behavior to Predict Consumer Behavior and Attitudes: A Case Study of Taiwanese Consumers on the Bonyo Tourism-Sharing Platform. - Liu, Jiliang; Sun, JunPing; Thiombiano, Dramane (Technium Social Sciences Journal, 2025)
This study examines the use of internet-based sharing economy platforms by Taiwanese tourists who purchase travel itineraries in Japan. The findings corroborate the extended Theory of Planned Behavior (TPB) model, demonstrating its effectiveness in explaining consumer purchase intentions within the sharing economy, particularly in the utilization of idle resources. Results indicate that positive consumer attitudes and perceived behavioral control significantly influence the likelihood of purchasing idle resources. By incorporating additional variables, this study extends the traditional TPB/TRA framework, enhancing its explanatory power and predictive accuracy. Among the three core TPB variables, perceived behavioral control emerges as the strongest predictor of purchasing idle resource-based products, followed by behavioral attitudes, aligning with previous research on subjective norms and perceived control in the sharing economy. This study contributes to the literature by demonstrating that consumers’ emphasis on idle resources positively impacts attitudes, subjective norms, perceived behavioral control, and purchase intentions in network-based sharing economy platforms. The findings suggest that Taiwanese consumers' willingness to purchase idle resource-based products enhances their engagement with sharing economy platforms, further expanding the adoption of idle resource services. Additionally, this study highlights the role of idle resources in fostering business innovation and sustainability. Given that young people and students represent the primary consumer demographic, policymakers should implement targeted policies to raise public awareness of the economic and environmental benefits of idle resource utilization. To promote sustainable consumption and optimize resource efficiency, future business models should prioritize integrating idle resources into sharing economy platforms. Keywords: Sharing economy platform; Idle resources; Theory of Planned Behavior; Structural equation modeling, Taiwan, Japan